2021
DOI: 10.1111/jth.15232
|View full text |Cite
|
Sign up to set email alerts
|

Biological stratification of clinical disease courses in childhood immune thrombocytopenia

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…From a large, nationwide study of children with newly diagnosed ITP, we know that some clinical and laboratory characteristics are associated with response to IVIg, like a preceding infection and Fc gamma receptor profile 7 . Based on this trial a prediction score was composed that not only predicted clinical course but also was able to predict a higher likelihood of response to IVIG 18,19 . Anti glycoprotein Ib/IX antibodies have been supposed to predict a lower response rate to IVIg by some studies, 20 but this was not confirmed by others 7 .…”
Section: Case Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a large, nationwide study of children with newly diagnosed ITP, we know that some clinical and laboratory characteristics are associated with response to IVIg, like a preceding infection and Fc gamma receptor profile 7 . Based on this trial a prediction score was composed that not only predicted clinical course but also was able to predict a higher likelihood of response to IVIG 18,19 . Anti glycoprotein Ib/IX antibodies have been supposed to predict a lower response rate to IVIg by some studies, 20 but this was not confirmed by others 7 .…”
Section: Case Discussionmentioning
confidence: 99%
“…7 Based on this trial a prediction score was composed that not only predicted clinical course but also was able to predict a higher likelihood of response to IVIG. 18,19 Anti glycoprotein Ib/IX antibodies have been supposed to predict a lower response rate to IVIg by some studies, 20 but this was not confirmed by others. 7 Data on the prediction of response to other agents in children are very scarce, so further research is needed.…”
Section: Predicting Refractory Itpmentioning
confidence: 92%
“…1 Much effort is invested in elucidating the etiology of ITP and prediction of ITP prognosis. 3 Previous results showed that oxidative stress could be involved in ITP development, similar to other diseases of autoimmune etiology. 4 Oxidative stress is usually defined as an imbalance between production and elimination of reactive oxygen and/or nitrogen species (ROS/RNS), due to increased production of ROS/RNS or/and impaired function of the antioxidative defense system.…”
Section: Introductionmentioning
confidence: 93%
“…7 Oxidative modification of proteins, such as oxidation of amino acid residues or oxidation by addition of aldehydes, may induce conformational alterations, formation of antigenic determinants, and initiation of autoantibody production. 3 Furthermore, ITP platelets have lower intracellular antioxidative capacity, and an increased level of pro-oxidants augments expression of NLRP3 inflammasome and interleukin (IL)-1β production. 8 Blockage of NLRP3, as well as caspase-1, in ITP platelets reduced production of IL-1β and pyroptosis, thus defining the ROS-NLRP3-caspase-1 signaling cascade in ITP development.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets have been observed to shed microparticles from their membrane during platelet activation and platelet apoptosis [47,48]. In ITP, a (viral) infection often precedes the onset of the disease, especially in children [58,59]. Such a preceding infection could be an initial trigger for platelets to release PMPs.…”
Section: The First Hitmentioning
confidence: 99%